Photochromic/electrochromic strain sensor with a fast and reversible light-printing ability. Issue 10 (28th February 2023) - Liang, Jundang; Li, Botian; Gai, Xiaodong; Li, Ning; Wang, Jian; Zhang, Yichi; Zhou, Qiong; Sun, Yuchao
Abstract : A strain sensor with photochromism and electrochromism was designed and fabricated based on the composite of MoO3− x and PEDOT:PSS; the strain sensor exhibited the performance of fast light printing and electroerasing. Abstract : The excessive use of paper causes serious resource consumption and environmental pollution. Environmentally friendly light printing based on a photochromic system with the advantages of being noncontact, rapid, and inkless has attracted increasing attention; however, several problems need to be addressed, such as slow discoloration and irreversibility. In this work, a composite of MoO3− x inorganic nanorods and the conductive polymer poly(3, 4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) was employed as a color-changing electrode, and a photochromic/electrochromic strain sensor (PESS) was obtained by assembling the color-changing electrode with an organohydrogel electrolyte and a flexible indium tin oxide (ITO) film. Due to the photochromic/electrochromic effect of MoO3− x and the conductivity of PEDOT:PSS, the sensor turned cyan-blue under UV irradiation or a negative bias voltage, and it could be rapidly bleached by applying a positive bias voltage. The photochromic/electrochromic behavior of the PESS could be optimized by tuning the amount of PEDOT:PSS, and the device could perform cyclic light printing/electroerasing with a fast and stable response. Moreover, the flexible strain sensor could be utilized to monitor mechanical strain by translating a series of deformations into electrical signals. The properties of photochromism/electrochromism and strain sensing make the device potentially applicable to outdoor wearable devices capable of light-based printing.